Fungal endocarditis after type a dissection, a positive outcome from Candida parapsilosis prosthetic aortic valve endocarditis and aortic graft infection: A testament to multidisciplinary practice. (November 2021) - Collins, Fredrika; Wenlock, Rhys D.; Curtis, Sally; Hyde, Jonathan; James, P. Rachael
Highlights: Fungal endocarditis is increasing in prevalence and remains challenging to manage both acutely and in the chronic phase. Dual anti-fungal therapy and timely operative management are the mainstays of effective treatment. A prolonged multidisciplinary approach is important in managing these complex patients. Abstract: Fungal endocarditis is associated with a very poor prognosis (mortality in excess of 50%) and the incidence is increasing due, in part, to the increased implantation of intra-cardiac devices and valve replacements. Diagnosis and treatment remain challenging, with the need for prolonged courses of dual, parenteral anti-fungal therapy that have several drug-drug interactions and side effects that require protracted monitoring. Moreover, there is uncertainty on the optimal management strategy for fungal endocarditis as, given its rarity, much of the evidence comes from small observational studies. We report a case of Candida parapsilosis prosthetic valve endocarditis and aortic graft infection necessitating a high-risk redo aortic valve replacement. This case illustrates the important role of the multidisciplinary Endocarditis Team in achieving a good outcome, despite year-long treatment and geographical separation of patient from the regional centre and Endocarditis Team expertise.